Short Communication: Use of Geographic Information System for mapping of Aquilaria malaccensis land suitability in North Sumatra, Indonesia - RAHMAWATY RAHMAWATY; SINTIKE FRASTIKA; RUTH MARIA ELTIANA MARPAUNG; RIDWANTI BATUBARA; ABDUL RAUF (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rahmawaty,  Frastika S, Marpaung RME,  Batubara R,  Rauf A. 2019. Short Communication: Use of Geographic Information System for mapping of Aquilaria malaccensis land suitability in North Sumatra, Indonesia. Biodiversitas 20: 2561-2568.  The Geographic Information System (GIS) can be applicated in the field of forestry and agriculture, such as for mapping as part of land evaluation. The land suitability of Aquilaria malaccensis in the agroforestry land of North Sumatra Province is important.  Commonly, A. malaccensis were planted by the community in Langkat and Deli Serdang District. This study aimed to map the land suitability for A. malaccensis in Telaga Village, Sei Bingai Sub District, Langkat District, Peria-ria Village and Sari Laba Jahe Village, Biru-biru Sub District, Deli Serdang District. A survey method was used to collect soil samples in the field. Land suitability classification (LSC) for A. malaccensis was evaluated based on the matching method.  The results showed that the actual land suitability classes for A. malaccensis in Telaga Village were moderately suitable (S2) and marginally suitable (S3). The actual land suitability classes for A. malaccensis in Peria-ria Village and Sari Laba Jahe Village were moderately suitable (S2), marginally suitable (S3) and not suitable (N). There were several limiting factors in land suitability evaluation in the area, namely: nutrient retention (nr), erosion hazard (eh), and root zone medium (rc).